2019
DOI: 10.3390/nu11051068
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Cell Cycle Regulation in the Antitumoral Action of Ocoxin

Abstract: Nutritional supplements which include natural antitumoral compounds could represent safe and efficient additives for cancer patients. One such nutritional supplement, Ocoxin Oral solution (OOS), is a composite formulation that contains several antioxidants and exhibits antitumoral properties in several in vitro and in vivo tumor conditions. Here, we performed a functional genomic analysis to uncover the mechanism of the antitumoral action of OOS. Using in vivo models of acute myelogenous leukemia (AML, HEL cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In hepatocellular carcinoma, addition of OOS provoked an increase in the amount of cyclin B1 that accompanied cell cycle arrest in G2 [70]. An unbiased microarray study performed on in vivo lung cancer and acute myeloid leukemia cells derived from xenografts prepared in mice, followed by functional transcriptomic evaluation revealed the cell cycle-related functions as the major target functions affected by OOS [66]. These studies confirmed the regulation of p27 and the Rb pathway by OOS in both types of xenografted tumors.…”
Section: Mechanism Of Action Of Oossupporting
confidence: 52%
See 2 more Smart Citations
“…In hepatocellular carcinoma, addition of OOS provoked an increase in the amount of cyclin B1 that accompanied cell cycle arrest in G2 [70]. An unbiased microarray study performed on in vivo lung cancer and acute myeloid leukemia cells derived from xenografts prepared in mice, followed by functional transcriptomic evaluation revealed the cell cycle-related functions as the major target functions affected by OOS [66]. These studies confirmed the regulation of p27 and the Rb pathway by OOS in both types of xenografted tumors.…”
Section: Mechanism Of Action Of Oossupporting
confidence: 52%
“…The effect of OOS on the cell cycle, as identified in the biochemical [65] and the in silico analyses [66], opens an interesting possibility for its application in a particular subtype of breast cancer. In fact, hormonal breast tumors, characterized by the presence of estrogen and progesterone receptors, are particularly sensitive to the action of CDK4/6 inhibitors.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormality of cell cycle litter-controlling factors is the main reason for the uncontrolled proliferation of cancer cells and the resistance of apoptotic cells can easily lead to the drug resistance of cancer cells. 34,36 Our data show that fucoidan induced the accumulation of SKOV-3 and Caov-3 cells in the G0/G1 phase, which was accompanied by a decreased numbers of cells in the S and G2/M phases. At the same time, fucoidan increased the level of cyclin-dependent kinase inhibitor 1A (P21) and decreased the Rb phosphorylation at Ser795.…”
Section: Discussionmentioning
confidence: 66%
“…34 Many growth factors, cytokines, hormones, and oncogene products regulate DNA metabolism through the cell cycle. 35,36 Studies of the cell cycle have deepened the understanding of the mechanism of tumorigenesis. As an antineoplastic drug, fucoidan has been found to induce G0/G1 phase arrest in SKOV-3 and Caov-3 cells (Figure 2A).…”
Section: Fucoidan Provoked Cell Cycle Arrest In Oc Cellsmentioning
confidence: 99%